Irrigation scheduling and superabsorbent polymers for enhancing productivity and improving plant water dynamics of kharif baby corn (Zea mays) - SHWETA; ASHOK KUMAR; ANITA KUMARI; NEELAM; MEENA SEHWAG; KAMLA MALIK; RENU MUNJAL (The Indian Journal of Agricultural Sciences)
The present study was carried out during rainy (kharif) seasons of 2019 and 2020 at Research Farm of Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to evaluate the impact of polymers with irrigation on baby corn (Zea mays L.) crops. The experiment was laid out in a split-plot design (SPD) with four irrigation [(One irrigation at sowing (I1); Two irrigation at sowing, knee high stage (I2); Two irrigation at sowing, before tasseling (I3), Three irrigation at sowing, knee height, before tasseling (I4)] in main plots and four polymer treatments [(No polymers or control (P0); Pusa Hydrogel @2.5 kg/ha (P1); Pusa Hydrogel @5 kg/ha (P2); Gondkatira @5 kg/ha (P3)] in subplot. The baby corn yield decreased by 20.99 and 25.50% from I4 to I3, 22.75 and 35.20% from I4 to I2, and 27.47 and 48.89% from I4 to I1 during the study period, first and second year, respectively. The polymer treatment was used to increase the baby corn yield. The yield was increased by 27.16, 133.09; 52.62 and 165.98 and 8.38,104.9. By application of hydrogel @2.5 kg/ha, hydrogel @5.0 kg/ha and gondkatira @5 kg/ha over to no polymers, during the first and second year, respectively. This might be because of the water that is available when it is dry, which would help avoid the delays in emergence and keep the water available for longer. The application of gondkatira in baby corn crops increased the water productivity by 22.25% (first year), 79.97% (second year) while hydrogel @5 kg/ ha increased 43.14 and 134.28% during first and second year of study, respectively. Water stress or one irrigation at sowing has a lower Fv/Fm (maximum quantum efficiency of PS II) (0.678 and 0.676) ratio than to no stress or three irrigations (0.682 and 0.676).